PERAN PETUGAS TINDAK INTERNAL DALAM PENEGAKAN KODE ETIK SATUAN POLISI PAMONG PRAJA KABUPATEN OGAN KOMERING ULU TAHUN 2023–2024 - Husien Yusuf; Yahnu Wiguno Sanyoto; Rahmat Saleh; Eva Susanti (PT. Hasba Edukasi Mandiri, 2026)
This study examines the role of Internal Control Officers (Petugas Tindak Internal/PTI) in the implementation of the code of ethics enforcement within the Civil Service Police Unit (Satuan Polisi Pamong Praja/Satpol PP) of Ogan Komering Ulu Regency during the 2023–2024 period. The research problem arises from the continued occurrence of disciplinary violations among personnel, which have implications for declining organizational performance and public image. The purpose of this study is to assess the effectiveness of PTI’s role while also identifying factors that support and hinder its implementation. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and document analysis. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the functions of PTI in supervision, guidance, and enforcement of the code of ethics have been carried out relatively effectively through socialization activities, inspections, and the gradual application of sanctions. Challenges remain in the form of limited human resources and the suboptimal utilization of supervisory technology. The study underscores the importance of strengthening a sustainable and modernized internal supervision system to enhance discipline and professionalism among Satpol PP personnel.members.